Forecast changes in the productivity of plant communities in the Pre-Urals Steppe site of Orenburg State Nature Reserve (Russia) in extreme drought conditions using NDVI - Nikolay I. Fedorov; Tatjana L. Zharkikh; Oksana I. Mikhailenko; Rafilia T. Bakirova; Vasiliy B. Martynenko (Nature Conservation Research: Заповедная наука, 2019)
The normalised-difference vegetative index (NDVI) seasonal dynamics of 15 types of vegetation communities in dry 2010 and in 2016 with a favourable weather conditions was studied in the Pre-Urals Steppe site where the Programme on establishing a semi-free population of the Przewalski's horse Equus ferus przewalskii in Orenburg State Nature Reserve started. The NDVI seasonal dynamics in a year with normal weather conditions includes four main phases including the 1st phase of spring NDVI increasing, the 2nd phase of the productivity maximisation of the dominant vegetation, the 3rd phase of the summer progressive decrease in photosynthetic activity in response to the heat and lack of moisture, the 4th phase of low photosynthetic activity lasting from midsummer to the late autumn. The dependence of NDVI on vegetation productivity during its maximum development in the Pre-Urals Steppe in 2016 was described by the linear regression equation. Vegetation productivity on 20 June 2010 and that on 20 June 2016, calculated by the linear regression equation, were compared. The comparison revealed that in 2010, the decline in productivity during vegetation maximum development varied between 19% and 65% depending on the type of plant community. The following plant communities were the least resilient to drought: communities of fallow lands on the locations of previous true steppes, communities which appeared under the influence of overgrazing in the locations of the previous true steppes and the communities of meadow-steppes. Good moistening resulted in a slight decline in productivity communities located in topographical depressions. Productivity of plant communities with early-spring growth of dominating species declined to a lesser degree as the communities are located on a well-warmed surface. Some biological features of the Caragana frutex + Spiraea crenata vegetation type also result in the less decline in productivity. The NDVI coefficient does not accurately reflect productivity at the end of the growing season. Therefore, patterns of declines in productivity of similar vegetation types during the drought in Trans-Urals region in 1998 were used to project the autumn decline in vegetation productivity during the drought in the Pre-Urals Steppe. Based on these findings, the average vegetation productivity in the Pre-Urals Steppe in autumn in dry 2010 were four to five times lower than that during the maximum plant development in 2016 which had favourable weather conditions. As the height of vegetation considerably reduces during drought, the availability of pasture forage may sharply drop in winter, especially if a deep snow cover accumulates and unevenly distributes according to terrain relief. In the Pre-Urals Steppe, only some steppe communities, covering about 20% of the area, are the most accessible to supply Przewalski's horses with dry pasture forage in winter. Projecting the winter supply of pasture forage after a severe drought should be based on the assumption that the forage availability may reduce by 8 to 10 times as compared with calculated summer productivity in a year with favourable weather conditions. In this regard, there is a need to make stocks of hay for feeding horses in winter after a drought. For potentially repeated droughts the sufficient amount of hay to feed Przewalski's horses in the Pre-Urals Steppe over two winter seasons should be stocked in years with normal precipitation as it will be difficult to make the stock in a dry year. For a final assessment of the accessibility of winter pasture forage stock for Przewalski's horses in the Pre-Urals Steppe, some additional field studies of productivity of the main vegetation types at the end of the growing season using the harvest method are necessary as well as an analysis of the distribution and height of snow cover on the territory in years with high winter precipitation.